2016
DOI: 10.32677/ijch.2016.v03.i02.007
|View full text |Cite
|
Sign up to set email alerts
|

Circulating 25-hydroxyvitamin D status in apparently healthy adolescents and its association with body mass index in Puducherry population

Abstract: Background: Several earlier studies were focused on Vitamin D status and insulin resistance in diabetes mellitus in adult population. However, very few studies have been done among the healthy adolescents associating Vitamin D status with body mass index (BMI) (anthropometric marker of central obesity). Objective: To examine the concentration of 25-hydroxyvitamin D (25[OH]D) in apparently healthy adolescent and its association with BMI in apparently healthy adolescents (12-19 years age group) of Puducherry reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…2 r = -0.736) are in agreement with many previous study. [22][23][24] The accumulation of visceral fat results in an increased risk of metabolic and cardiovascular complications. 25 Arunabh et al 26 studied a group of women between 20-80 years old and showed that serum Vitamin D levels decreased with an increase in the amount of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…2 r = -0.736) are in agreement with many previous study. [22][23][24] The accumulation of visceral fat results in an increased risk of metabolic and cardiovascular complications. 25 Arunabh et al 26 studied a group of women between 20-80 years old and showed that serum Vitamin D levels decreased with an increase in the amount of adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, changing lifestyle, urbanization and modernization has led to possible reduction of people being exposed to direct sunlight and inadequate intake of dietary vitamin D. 14 As a result, vitamin D deficiency or insufficiency prevails in all over the Indian subcontinent. 15,16,17 As per available literatures not too many studies have been done in this context, especially in North Bengal region of West Bengal, India. So, this study was undertaken to find out the correlation between vitamin D status and glycaemic status of individual and determine the risk of impaired glucose tolerance depending on vitamin D status, independent of other factors.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%